Evaluation of a Colorimetric PCR-Based Assay To Diagnose Plasmodium falciparum Malaria in Travelers - Zhong, Kathleen J. Y. (American Society for Microbiology, 1999)
New diagnostic tests are needed to facilitate the diagnosis of Plasmodium falciparum malaria in the returned traveler. We performed a blinded evaluation of a nonisotopic colorimetric PCR-based assay (Digene SHARP Signal System) and compared the results with those obtained by microscopy and nested PCR for the detection of P. falciparum malaria in 150 febrile travelers. By using nested PCR as the reference standard, the colorimetric assay had a sensitivity of 100% and a specificity of 95.4% for the detection of P. falciparum. This PCR-based nonisotopic assay is a rapid, sensitive, and specific method for the detection of falciparum malaria in returned travelers.